Islam pada Masa Tiga Kerajaan Besar - Munazzalurrohmi, Muhammad; Al Ghatnini, Raeed Awadh Saeedh; Fathoni, Abd Rofi (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The development of Islam during the periods of the Ottoman Empire, Mughal Sultanate, and Safavid Dynasty reflects the diversity and complexity of religious, political, and cultural influences that shaped Islamic civilization. The purpose of this study is to analyze how these three empires interacted, adapted, and contributed to the growth of Islam and related cultures. This research uses a qualitative method through reviewing various historical sources and scholarly literature. The findings indicate that the Ottoman Empire was a major protector and promoter of Sunni Islam, with policies promoting cultural and scientific advancements; the Mughal Sultanate emphasized religious tolerance and produced remarkable arts and architecture, strengthening India’s cultural landscape; while the Safavid Dynasty established Shia Islam as the state religion and made significant contributions in arts and religious thought. These empires not only engaged in conflicts and diplomatic relations but also exchanged cultural and religious ideas, which enriched Islamic civilization. This study contributes to a better understanding of how Islam developed and spread during the golden ages of these three empires by presenting a detailed analysis of their interactions and achievements.